SUGARCANE CULTIVATION IN INDIA: UNVEILING COSTS, CHALLENGES, AND PATHWAYS TO SUSTAINABLE FARMING IN THENI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The primary source of sugar in India is sugarcane, which is also a significant cash crop. The states that produce the most sugarcane in India include Tamil Nadu, Uttar Pradesh, Bihar, Assam, Haryana, Gujarat, and Andra Pradesh. India is regarded as a sugar behemoth, with more than 500 sugar mills and one of the biggest sugar exporters. A research was carried out in the Theni District, and 374 farmers were contacted to gather information about the costs associated with production and the challenges that farmers encountered during that period. Additionally, research offers a solution to farmers' difficulties.